Optimalisasi Bahan Alam Lokal dalam Pendampingan Pembuatan Ecoprint bagi Siswa Sekolah Dasar Sebagai Upaya Penguat Karakter Peduli Lingkungan - Fatimah, Siti; Subekti, Aqlan; Mudhofar, Wali; Rosid, Masrukhil; Ma’ruf, Ngaenun; Fauziyah, Asnaful; Damayanti, Silvia; Puspitasari, Fadilah; Turohmah, Irfa; Nabilah, Nurul Khadifatun; Suhadi, Ahmad; Ramadani, Novita; Zamzama Billa, Zahro Adha; Pramono, Ibnu Jati (Jurnal Inovasi dan Pengabdian kepada Masyarakat (JIPMas), 2025)
Environmental pollution has become a crucial problem, necessitating efforts to address it. This assistance aims to train students in the making of ecoprints as an effort to introduce local potential and strengthen environmentally conscious character. The assistance was carried out on August 20, 2024, to 53 students at SD Negeri 1 Karanggayam, Kebumen Regency. The assistance phase was carried out in four steps: planning, preparation, implementation, and evaluation. This assistance activity resulted in the finding that 100% of students have learned ecoprint techniques and were able to build environmental awareness among students.